Jorge Lafforgue (editor). Explicar la Argentina. Ensayos fundamentales. Buenos Aires, Taurus, 2009, 565 p. ISBN 978-987-04-1089-8. - Ferraro, Liliana (2009)
Fil: Ferraro, Liliana. Universidad Nacional de Cuyo